Effectiveness of Career Guidance Program in Improving Students’ Job Readiness - Sota Yamamoto; Riko Kobayashi; Samantha Gonzales (International Journal of Educational Narratives, 2025)
Background. With increasing competition in the labor market, students must possess not only academic knowledge but also the practical skills and emotional readiness to transition into professional environments. Purpose. This study aims to evaluate the effectiveness of a career guidance program in improving students’ job readiness, focusing on key factors such as self-efficacy, communication skills, and career decision-making abilities. Method. A quantitative research design was employed, using pre- and post-surveys to assess the program’s impact on a sample of 300 high school students. The data were analyzed using descriptive statistics and paired sample t-tests. Results. The results indicate a significant improvement in students’ job readiness after participating in the career guidance program. The most notable gains were observed in self-confidence, the ability to make informed career decisions, and the development of job-search skills. Conclusion. The study concludes that career guidance programs are highly effective in equipping students with the necessary skills and mindset to succeed in the job market. Schools and educational institutions should prioritize the implementation of such programs to better prepare students for future employment opportunities.